Research on Power Battery Closed-loop Supply Chain Recycling Strategy Considering Service Level - Zhang, Yuxin; Lei, Xiaonan; Zheng, Bokai; Yan, Dongdong (Scientific Journal of Technology, 2026)
Against the backdrop of the rapid development of the new energy vehicle industry, the recycling of waste power batteries has gradually become a research hotspot. The service level of recycling enterprises and the energy density of power batteries are key factors influencing the recycling efficiency and overall profit of the closed-loop supply chain. Taking the closed-loop supply chain of power batteries as the research subject, this paper considers the energy density of power batteries and the recycling service level, and constructs three game models of closed-loop supply chains where power battery manufacturers, new energy vehicle enterprises, and third-party recycling enterprises are responsible for recycling, respectively. Through a comparative analysis of the optimal decisions among different models, it is found that improving the recycling service level can significantly enhance the overall recovery rate and the total profit of the supply chain. Among the three modes, the recycling mode led by power battery manufacturers exhibits the greatest advantages in both the recovery rate and the total system profit. This study provides a theoretical basis for the selection of recycling modes and the optimization of service decisions in the closed-loop supply chain of new energy power batteries.